1970
DOI: 10.1172/jci106241
|View full text |Cite
|
Sign up to set email alerts
|

Ionized calcium in normal serum, ultrafiltrates, and whole blood determined by ion-exchange electrodes

Abstract: A B S T R A C T Ion-exchange calcium electrodes represent the first practical method for the direct measurement of ionized calcium [Ca"+] These studies were included as part of a symposium, January 1969 (1) and preliminary reports have appeared previously (2, 3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
189
2
4

Year Published

1971
1971
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(218 citation statements)
references
References 26 publications
9
189
2
4
Order By: Relevance
“…They rely on Ca 2þ ions to maintain their elongated structure and enable their adhesive functions (4)(5)(6)(7)(8). The normal physiological extracellular calcium level is 2.12-2.62 mM; with~40% of the Ca 2þ ions binding to proteins and~10% of them bound to various anions in complexes, the corresponding free calcium level is 1.16-1.31 mM (9)(10)(11). In cell culture, a wide range of Ca 2þ concentrations (even as low as 0.02 mM) are sometimes employed (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…They rely on Ca 2þ ions to maintain their elongated structure and enable their adhesive functions (4)(5)(6)(7)(8). The normal physiological extracellular calcium level is 2.12-2.62 mM; with~40% of the Ca 2þ ions binding to proteins and~10% of them bound to various anions in complexes, the corresponding free calcium level is 1.16-1.31 mM (9)(10)(11). In cell culture, a wide range of Ca 2þ concentrations (even as low as 0.02 mM) are sometimes employed (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the protein-bound fraction represents 30 to 55%, diffusible ionic complexes (e.g., bicarbonate, citrate, sulfate, phosphate lactate) 5 comprise approximately 5 to 15%, and approximately 50% is freely ionized. 6 Most of the protein-bound calcium is complexed to albumin, with the remainder binding to globulins. 5 Experiments by Moore 6 and McLean and Hastings 7,8 confirmed that ionized calcium accounts for the biologically active form of serum calcium and subsequently demonstrated the crucial role of ionized calcium in the calcium homeostasis of healthy individuals and patients with parathyroid abnormalities.…”
mentioning
confidence: 99%
“…5 Precision in ionized calcium measurement was revolutionized after the introduction of ion-selective electrodes 10 ; however, the clinical application of this technique was initially limited and delayed by its cost, susceptibility to errors, need to prevent CO 2 losses from the sample, and control of pH. 6 Advances in technology for direct measurement of ionized calcium have decreased the cost and improved its availability in the clinical setting since the 1980s. 11 A number of limitations remain, however, particularly in the outpatient setting, including the technical challenge of equipment maintenance, frequent electrode replacement with associated downtime, and redundancy of instrumentation and personnel, all leading to increased costs.…”
mentioning
confidence: 99%
“…Excessive aldosterone induces an expansion of extracellular fluid, which, in turn, may inhibit the tubular reabsorption of calcium in the kidney, thus increasing urinary calcium excretion. Hyperaldosteronism causes hypokalemic alkalosis, which may decrease serum ionized calcium (13). Both changes may lead to lowered serum calcium levels.…”
Section: Discussionmentioning
confidence: 99%